(untitled) (Research, Society and Development, 2022)
Objective: To estimate the consumption and quantity of unaltered antiretrivirals (ARV) eliminated into the environment and to carry out a literature research on aquatic ecotoxicological studies of ARV used in Brazil. Methodology: We requested from one of the ARV dispensing units in the city of Belo-Horizonte (BH) the amount of ARV dispensed in the years 2018-2019-2020. Considering the amount dispensed in 2020, the daily dose, and the elimination rate, the amount of drug in unchanged form in the environment was estimated. For entire municipality of BH and Brazil, we used epidemiological data were used regarding individuals using antiretroviral therapy (ART) in 2020, the proportion of people living with HIV using the main ART regimen, following the same estimation methodology used previously. Structured and individual searches were carried out for each ARV used in Brazil, relating it to ecotoxicology, through Google Scholar, National Center for Biotechnology Information and Scifinder, in addition to the use of the fass.se platform. Results: Four articles presented results of acute or chronic toxicity in ecotoxicological models involving ARV. Dolutegravir and efavirenz were found to be highly toxic in ecotoxicological models. In 2020, approximately 2,167kg of ARVs in unchanged form were released into the environment in BH. In Brazil it was 112,274kg. Conclusion: It is urgent to quantify the main ARV in water bodies. With these data together with ecotoxicological data it will be possible to establish risk criteria for possible measures to control or mitigate these contaminants in the environment, especially actions to improve wastewater/water treatment.